PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IXG SMP NEGERI 1 SURAKARTA TAHUN 2017/2018 - Supanti, S. (HISTORIKA, 2019)
Researchclass action aimstoundertand how the model thediscovery learning in learning social science to improve critical thinking n Junior High School 1  Surakrta grade IXG 2017/2018. The method of this research is a descriptive qualitative research result from the cllass in the form of treatment with subject of the research is grade IXG totaling 32 students, comprising 12 men and 20  women. Research data obtained from the observation of learning activities, the informant, documents and photographs of the value of the activities. Minimal standart pass social science class IXG 8,0 with Minimal standards clasikal 85%. After treatment for 3 cycle increased results achieved is the value ot test the ability of  think critically in cycle I : 62,50 %, cucle II : 81,25 %, and cycle III : 90,63  % wort average ciycle I : 76,92, cycle II : 80,76 and cycle III : 85,00. The value of the cycle capacity to critical thinking in discussion on the cycle I : 59,38%, cycle II : 84,38% and cycle III : 90,63%. The average value of students in cycle I : 81, cycle II : 83 and cycle III:88. Minimal standarts pass in cycle I : 78,12%, cycle II : 87,50 % andcycle III : 93,75%.